Efeito de antioxidantes na resistência de união de um sistema adesivo ao esmalte bovino tratado com peróxido de hidrogênio 35% - Paula, Felipe Augusto Ramirez de (2017)
When restoration is placed immediately after dental bleaching, the residual oxygen from the hydrogen peroxide degradation inhibits the polymerization of the resinous compounds, reducing the bond strength. Therefore, the objective of this study was to evaluate the influence of the application of antioxidant substances, 10% sodium ascorbate, 5% glutathione and 10% glutathione, on the bond strength of an adhesive system on the bovine enamel previously treated with 35% hydrogen peroxide. The antioxidant activity test by the DPPH free radical was performed to measure the antioxidant power of the experimental substances, using distilled water as a negative control. Enamel blocks of 111 healthy bovine incisors were randomly divided into five groups: without (C+) or with (C-) bleaching, with bleaching and application of solutions of 10% sodium ascorbate (ASC-10), 5% glutathione (GLUT-5) or 10% glutathione (GLU-10), for five minutes, and Filtek Z350 nanohybrid resin was applied in 1mm increments. In the monomers’ degree conversion test of the adhesive system, slices (1mm) of two specimens of each group were used for comparison with the adhesive system in the polymerized and non-polymerized states by Micro-Raman eletroscopy, operating with HeNe laser at 532nm. In the bond strength test, the blocks were sectioned until obtaining sticks of 1.0 mm2. The sticks were subjected to a traction of 0.5 mm/min in an universal testing machine. The fracture mode was analyzed and classified. The one-way ANOVA and Kruskal-Wallis tests, adopting a significance level of 5%, were performed for statistical analysis. ASC-10 showed better antioxidant activity (p<0.05). The application of the antioxidant substances did not influence the degree of conversion of the adhesive monomers (p>0.05). In the test of degree conversion, the C- group statistically inferior to others groups (p<0.05). In the bond strength test, GLUT-5 and GLUT-10 were statistically superior (p<0.05) than the C+. The ASC-10 and C+ groups did not show any statistical differences. Although ASC-10 showed better antioxidant activity and recovered the values of bond strength, GLUT-10 was more efficient than ASC-10 in reversing the effect of decrease of bond strength after the use of bleaching agents. There was prevalence of adhesive failure in all groups.